Escape the Simulation Room. (February 2021) - Sanders, Jennifer E.; Kutzin, Jared; Strother, Christopher G.
Background: Healthcare simulations are used at most academic facilities to improve knowledge and performance on critical and key concepts and can also be used to enhance competency andteamwork . Group simulation scenarios often have individual team leaders, but these scenarios require a team to work together to efficiently care for the patient. Escape rooms can be utilized inhealthcare as a fun educational activity to encourage teams to work together and think creatively to solve puzzles and challenges. One advantage of this type of activity in ahealthcare setting is to dissolve any hierarchy amongst the team and build the confidence of novice or more passive participants. Escape rooms in ahealthcare setting do not have to be medically themed to be effective, and rooms can be set up with minimal equipment. Aim: This article addresses the detailed steps required to set up ahealthcare themedescape room that has been shown to work well. It is applicable tohealthcare professionals and can be adapted for non-healthcare workers. Method: Based on theEscape Room video games and social activity phenomenon, teams compete to solve content-specific challenges to attain pieces of the final puzzle set forth by the instructors. Traditional quiz-type exercises, pictograms, and procedural based activities comprise the puzzles of the game. The first team to obtain all pieces of the final clue and put them together in the correct order in the shortest amount of time is deemed the winner. Gameplay is designed to conclude in approximately 20 minutes. Results and Conclusion: This game mimics interdisciplinaryteamwork environments. Participating in interactive collaborative learning environments enhances the overall learning experience, allowing learners to apply knowledge.